Analysis of sono-photodynamic effects with PpIX - in Vitro and in vivo studies - Ayala, Erika Toneth Ponce (2020)
Sono-photodynamic therapy (SPDT) is a relatively new and promising approach to cancer treatment, based on the combination of an sono-photoactive drug, low-intensity ultrasound and light. This combined therapy increases anticancer effects by the induction of cell death into deeper body regions. This study aims to analyze the mechanisms and effects of the sono-photodynamic (SPD) action on Protoporphyrin IX (PpIX) solutions and PpIX-loaded rat healthy liver. In vitro, PpIX 5μM solutions were irradiated with light (635 nm, 30-50 mW/cm2) (photodynamic (PD) action), ultrasound (1MHz, 1-2 W/cm2) (sonodynamic(SD) action) and the combination of both sources. This combination was carried out in three different ways: applying both sources simultaneously (SPD action) and applying one source after the other (PD+SD and SD+PD action). The absorption spectra of PpIX solutions recorded during irradiation, showed that the PpIX decay rate (k) induced by SPD action was approximately the sum of those induced by the PD and SD action (kSPD ≅ kSD + kPD). In vivo, rats were intraperitoneal injected with 5-aminolevulinic acid (ALA) at doses of 500 mg/kg body weigh to load the rat liver with higher concentration of PpIX. At 3h (time of optimum drug concentration in the liver) after injection, the PpIX-loaded livers were irradiated with light (635 nm, 180 ± 9 J/cm2) (PD action), ultrasound (1.0 MHz, 765 ± 38 J/cm2) (SD action), and the combination of both sources (SPD, PD+SD, SD+PD action). For these procedures, a single probe capable of irradiating light and ultrasound simultaneously was built. After 30 hours, animals were sacrificed, the livers were surgically removed and analyzed through scanned histological slides. The SPD and PD+SD action induced greater necrosis depth than either PD or SD action. These results suggested that the combined action could improve the drug decay rate, as well as having a greater scope than either PD or SD action, but it certainly must be more widely studied.